Paraquat poisoning: An unusual lung toxicity - Nitin Dhochak; Jhuma Sankar; Rakesh Lodha (Wolters Kluwer Medknow Publications, 2019)
Paraquat poisoning is an uncommonly faced but fatal poisoning. Paraquat gets accumulated in lung tissues by active absorption against concentration gradient and causes oxidative injury. We hereby, describe a fourteen years old boy admitted following ingestion of paraquat (approximately 10-15ml). Immediately after ingestion, child developed oral ulceration and recurrent vomiting. Since day 4 of ingestion the boy developed respiratory distress which worsened over the week requiring initiation of mechanical ventilation at very high settings. He was also treated with methylprednisolone pulse therapy for paraquat toxicity. There was transient improvement in oxygenation parameters following these therapies. Unfortunately, the hypoxemia worsened despite initial improvement and he finally succumbed on day 14 of illness. It appears that initiation of immunosuppressive therapy early in the course of ingestion even when the patient is apparently free of any respiratory complaints may alter the course of moderate to severe poisoning.